Integrating HBV, HCV and HIV screening in tuberculosis entry screening for migrants in the Netherlands. (13th November 2019) - Bil, J; Schrooders, P A G; Prins, M; Kouw, P M; Klomp, J H E; Scholing, M; Huijbregts, L; Sonder, G J B; Waegemaekers, T; Tostmann, A; ,
Abstract: We evaluated uptake and diagnostic outcomes of voluntary hepatitis B (HBV) and C virus (HCV) screening offered during routine tuberculosis entry screening to migrants in Gelderland and Amsterdam, the Netherlands, between 2013 and 2015. In Amsterdam, HIV screening was also offered. Overall, 54% (461/859) accepted screening. Prevalence of chronic HBV infection (HBsAg-positive) and HCV exposure (anti-HCVpositive) in Gelderland was 4.48% (9/201; 95% confidence interval (CI): 2.37-8.29) and 0.99% (2/203; 95% CI: 0.27-3.52), respectively, all infections were newly diagnosed. Prevalence of chronic HBV infection, HCV exposure and chronic HCV infection (HCV RNA-positive) in Amsterdam was 0.39% (1/256; 95% CI: 0.07-2.18), 1.17% (3/256; 95% CI: 0.40-3.39) and 0.39% (1/256; 95% CI: 0.07-2.18), respectively, with all chronic HBV/HCV infections previously diagnosed. No HIV infections were found. In univariate analyses, newly diagnosed chronic HBV infection was more likely in participants migrating for reasons other than work or study (4.35% vs 0.83%; odds ratio (OR) = 5.45; 95% CI: 1.12-26.60) and was less likely in participants in Amsterdam than Gelderland (0.00% vs 4.48%; OR = 0.04; 95% CI: 0.00-0.69). Regional differences in HBV prevalence might be explained by differences in the populations entering compulsory tuberculosis screening. Prescreening selection of migrants based on risk factors merits further exploration.